Self-Injury with Carbamazepine Intoxication in an Elementary School-Aged Child - Andrew Shieh; Natalie Schellpfeffer (Case Reports in Pediatrics)
Carbamazepine is a common anticonvulsant medication used to treat seizure disorders and is generally considered a safe medication. We describe the case of a 9-year-old female who presented with acute altered mental status and respiratory failure requiring mechanical ventilation. She was found to be intoxicated with carbamazepine through a urine drug test which was confirmed by bloodwork. After her medical condition improved, the patient admitted to self-injury through ingestion to cope with the death of a family member. She received a complete psychiatric assessment and was eventually discharged without permanent neurologic sequelae. To our knowledge, this is the first case of intentional self-injury with carbamazepine intoxication in an elementary school-aged child. When intoxication is suspected in children presenting with altered mental status, all medications available at home should be investigated. Preadolescent children may engage in nonfatal self-injury behavior, and diagnosis requires a high index of suspicion.